Associations of Household Solid Fuel Use With Falls and Fall-Related Injuries in Middle-Aged and Older Population in China: A Cohort Study - Xing Ming; Ruixiao Guo; Mengli Liu; Xiaoman He; Feifei Guo; Shengli Gao (Frontiers Media S.A., 2023)
Objective: This study evaluated the associations of solid fuels with incidence of falls and fall-related injuries.Methods: Data were taken from wave 1∼4 of the China Health and Retirement Longitudinal Study, including 15,651 participants aged 45 years and older. Modified Poisson regression was used to examine the associations of solid fuels with falls and fall-related injuries.Results: Modified Poisson regression analysis showed that solid fuels users for cooking had an increasing incidence of falls and fall-related injuries, with RR of 1.211 (95% CI: 1.124, 1.305) and 1.248 (95% CI: 1.107, 1.408); for heating had an incidence, with RR of 1.178 (95% CI: 1.062, 1.306) and 1.134 (95% CI: 0.963, 1.335); combined for cooking and heating, with RR of 1.247 (95% CI: 1.105, 1.408) and 1.185 (95% CI: 0.982, 1.431).Conclusion: Our study suggests that solid fuel use is associated with a higher incidence of falls and fall-related injuries among adults aged 45 years and older in China. It is necessary to restrict solid fuel use to reduce household air pollution and make stronger environmental protection policies to improve household environment.